An Immediate Death by Seat Belt Compression; a Forensic Medicine Report - Najari, Fares (Emerg (Tehran), 2015)
Although death is a gradual process, sometimes sudden death occurs in a fraction of a minute or seconds. Here we report a 49-year-old man without any underlying disease, which has instantly died in an accident scene due to compression of neck critical elements by a three-point seat belt. The examination of the body and the results of the autopsy, toxicology and pathology tests are described from the viewpoint of forensic medicine.